Multiple receptor-ligand interactions direct tissue resident gamma delta T cell activation - Witherden, Deborah A.; Ramirez, Kevin; Havran, Wendy L. (Frontiers in Immunology, 2014)
Gamma delta T cells represent a major T cell population in epithelial tissues, such as skin, intestine, and lung, where they function in maintenance of the epithelium and provide a crucial first line defense against environmental and pathogenic insults. Despite their importance, the molecular mechanisms directing their activation and function have remained elusive. Epithelial resident gamma delta T cells function through constant communication with neighboring cells, either via direct cell-to-cell contact or cell-to-matrix interactions. These intimate relationships allow gamma delta T cells to facilitate the maintenance of epithelial homeostasis, tissue repair following injury, inflammation, and protection from malignancy. Recent studies have identified a number of molecules involved in these complex interactions, under both homeostatic conditions, as well as following perturbation of these barrier tissues. These interactions are crucial to the timely production of cytokines, chemokines, growth factors and extracellular matrix proteins for restoration of homeostasis. In this review, we discuss recent advances in understanding the mechanisms directing epithelial-T cell crosstalk and the distinct roles played by individual receptor-ligand pairs of cell surface molecules in this process.